Eksplorasi Pengembangan Media Pembelajaran Ramah Anak Dalam Ranah Pendidikan Informal SD - Ismuwardani, Zakiyah; Rusilowati, Ani; Trimurtini (STAIN Bengkalis, 2025)
This study aims to explore the development of child-friendly learning media in the context of informal education at the elementary school level. The background of this study is based on the need for learning media that not only supports cognitive aspects but also considers the emotional and social comfort of children in a flexible and non-formal learning process. This study uses a Systematic Literature Review design by tracing various reputable international journal articles published in the last ten years. The analysis procedure was carried out through the stages of identification, selection, and synthesis of data to find patterns and trends in the development of child-friendly learning media in informal education environments. The results of the study show that effective learning media in this context generally have interactive characteristics, are adaptive to children's needs, and support game-based and experiential learning. This study emphasizes the importance of a humanistic and creative approach in designing learning media that is appropriate for the world of children outside the formal classroom. These findings are expected to form the basis for the development of more inclusive and sustainable learning media innovations